FUNGSI KOGNITIF PADA PASIEN TUMOR OTAK METASTASIS PASCA RADIASI WHOLE BRAIN RADIOTHERAPY DI DUA RS RUJUKAN KANKER INDONESIA - Rahmi Ardhini; Tiara Aninditha; Rini Andriani; Henry Riyanto Sofyan (PERDOSNI, 2020)
Brain metastases represent one of the most common neurological complications of systemic cancer, with an incidence was about 40%. Whole brain radiotherapy (WBRT) is a standard treatment to reduce tumor volume and increasing patient’s survival, but WBRT has a side effects due to radiation exposure to the brain parenchyma, including cognitive impairment. This was case series of 8 brain metastases patients, consist of 4 male and 4 female who have undergone radiation on April until June 2018. Cognitive function was assessed using Montreal Cognitive Assessment-Indonesian Version (MoCA-Ina) before and after WBRT. Collected data were age, sex, educational status, number of lesions, tumor site, clinical symptoms, Karnofsky Performance Status (KPS) score, extracranial metastases, radiation dose, primary cancer, hypertension, and diabetes mellitus. Most are multiple lesions and located in parietal lobe. The most common symptom was cognitive impairment. Seven patients already experienced cognitive impairment before WBRT and mostly have improved cognitive function after WBRT. Memory function was impaired in all subjects before WBRT that did not improved afterwards, but other domains including attention, language, executive function, and visuospatial were improved after WBRT. Key word: brain metastases, cognitive function, whole brain radiotherapy.